What Is The New and Sensitive Tumor Marker for Detection of Different Kidney Tumors? Modern Study to Isolation, Purification and Characterization of N-Acetyl Galactosamine Binding Lectin From Sera Of Patients With Kidney Cancer - Jasim, Rasha Hasan; Hasan, Dr. Hathama Razooki; Husain, Dr. Majed Khadum (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
The present study was designed to investigate lectins in sera of patients with kidney tumors, in addition to non tumoral kidney disease patients. Fifty five patients of malignant kidney tumors were enrolled in addition to 23 patients of benign kidney tumors, and 18 patients of non tumoral kidney diseases used as control groups, in addition to 46 healthy individuals were also investigated. The age of patients and healthy individuals were 10-90 years. The measurement of total serum proteins revealed significant (p < 0.001) decrease in patients of malignant tumors when compared with those of benign, non tumoral diseases, and healthy individuals. The conditions of the hemagglutination assay of serum lectin activity were optimized. They were Tris buffer of 20 mM and pH 7.4, 60 mM CaCl2, 800 Âµg of defatted serum, 30 ËšC for serum samples, 60 minutes for serum samples, and human blood of group A+ suspension with 1.4 optical density. The measurement of the specific hemagglutination activity of lectins demonstrated significant (p < 0.001) elevation in patients of malignant tumors when compared with those of other patients and healthy individuals. Lectin activity was pointed out to be significantly (r = 0.767 at p < 0.0005) positively correlated with stage of malignancies. The cutoff value of the specific hemagglutination activity was found to equal 6 SHU for discriminatory malignant kidney tumors. Serum lectins activity were indicated to be inhibited by galactose, mannose, lactose, and N-acetyl galactosamine. Purification of lectin from sera of patients with malignant kidney tumors by affinity chromatography with the use of silver stain revealed N-Acetyl Galactosamine Binding Lectin (GalNAcBL). The purified folds and the yield was 178 with 32.4%. The polyacrylamide gel electrophoresis (PAGE) of purified lectin demonstrated one band consisted lectin activity. The approximate molecular weight of GalNAcBL was determined and found to be 63.83. Purified lectin was characterized through the assessment of the capability to agglutinate RBCs, inhibition by EDTA, pH dependency, thermal dependent, and carbohydrate contents. GalNAcBL were observed to be calcium dependence lectins (C-type). These results suggest that the diagnosis of the specific hemagglutination activity of lectin is promising biomarker for discrimination of malignant kidney tumor patients and the purified lectin could be introduced in the field of biomarkers.Â